The Mount Merapi Eruption Disaster Education Program Increases Community Knowledge in the Working Area of the Ngemplak II Sleman Community Health Center - Asmarani, Fajarina Lathu; Syafitiri, Endang Nurul; Novika, Almira Gita; Ervindo, Ervindo (Jurnal Keperawatan Respati Yogyakarta, 2025)
Indonesia is prone to volcanic eruptions, with Mount Merapi in Yogyakarta being one of the most active volcanoes in the country. Despite the risks, the community's preparedness for volcanic eruptions is still lacking. This study contributed to evaluate the effectiveness of an educational program in improving community preparedness for Mount Merapi eruption disasters in the Ngemplak II Puskesmas working area. A quasi-experimental design with a pretest-posttest one-group design was used, involving 66 respondents from Widodomartani Village. The educational program consisted of a lecture, discussion, poster installation, and booklet distribution. The results showed a significant increase in community knowledge after the educational program, with a Wilcoxon test value of 0.000. The study concludes that the educational program is effective in improving community preparedness for Mount Merapi eruption disasters. The findings suggest that a comprehensive educational program that combines different media can increase community knowledge and preparedness for volcanic eruptions. The study recommends the implementation of similar educational programs in disaster-prone areas to enhance community resilience.